Computational Biomechanics for Medicine - Miller, Karol; Nielsen, Poul.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Mathematical modelling and computer simulation have proved tremendously successful in engineering. One of the greatest challenges for mechanists is to extend the success of computational mechanics to fields outside traditional engineering, in particular to biology, biomedical sciences, and medicine. The proposed workshop will provide an opportunity for computational biomechanics specialists to present and exchange opinions on the opportunities of applying their techniques to computer-integrated medicine. For example, continuum mechanics models provide a rational basis for analysing biomedical images by constraining the solution to biologically reasonable motions and processes. Biomechanical modelling can also provide clinically important information about the physical status of the underlying biology, integrating information across molecular, tissue, organ, and organism scales. The main goal of this workshop is to showcase the clinical and scientific utility of computational biomechanics in computer-integrated medicine.
Computational biomechanics of soft tissues and flow -- Patient-Specific Modelling of Cardiovascular and Respiratory Flow Problems – Challenges -- MRI Tissue Segmentation Using a Variational Multilayer Approach -- Mapping Microcalcifications Between 2D Mammograms and 3D MRI Using a Biomechanical Model of the Breast -- Accuracy of Non-linear FE Modelling for Surgical Simulation: Study Using Soft Tissue Phantom -- Patient-Specific Hemodynamic Analysis for Proximal Protection in Carotid Angioplasty -- Cortical Surface Motion Estimation for Brain Shift Prediction -- Method for Validating Breast Compression Models Using Normalised Cross-Correlation -- Can Vascular Dynamics Cause Normal Pressure Hydrocephalus? -- Computational biomechanics of tissues of musculoskeletal system -- Computational Modelling of Human Gait: Muscle Coordination of Walking and Running -- Influence of Smoothing on Voxel-Based Mesh Accuracy in Micro-Finite Element -- Biomaterial Surface Characteristics Modulate the Outcome of Bone Regeneration Around Endosseous Oral Implants: In Silico Modeling and Simulation -- Subject-Specific Ligament Models: Toward Real-Time Simulation of the Knee Joint -- Ergonomic Assessment of Hand Movements in Laparoscopic Surgery Using the CyberGlove® -- Effects of Fetal Head Motion on Pelvic Floor Mechanics -- Novel Monitoring Method of Proximal Caries Using Digital Subtraction Radiography.
Keywords: Biomedical engineering; Biophysics; Biological physics; Computer simulation; Surgery; Biomedical Engineering and Bioengineering; Biological and Medical Physics, Biophysics; Simulation and Modeling; Surgery